Photodestruction of acetylcholinesterase. - Bishop, W H (1980)
Ultraviolet irradiation of 11S acetylcholinesterase (acetylcholine acetylhydrolase, EC 3.1.1.7) produces a loss of tryptophan fluorescence which is best described as the sum of two separable first-order processes, one much more rapid than the other. In addition, the enzyme undergoes an all-or-none inactivation that is monotonically first order. Simultaneous with activity loss, photoscission takes place and results in a molecular weight drop of 1 x 10(5); this decrease is first order with a rate constant identical to that for enzymatic inactivation. These processes are accompanied by apparent conformational changes, as shown by circular dichroic and difference absorption spectra. The relative photochemical inactivation efficiency of incident light is unity when corrected for the wavelength dependence of fluorescence excitation, which is consistent with an efficient Förster resonance transfer of energy among the aromatic chromophores. The extreme sensitivity of acetylcholinesterase to photodestruction upon photon absorption and the several events that follow it not only suggest that these findings might be a basis for a useful molecular probe of the structure of this enzyme, but also indicate that additional care should be taken when conducting spectroscopic studies in the UV region.